Seeds for Needs – Papua New Guinea - Zanzanaini, Camilla (Bioversity International, 2014)
‘Seeds for Needs’ is a global initiative led by Bioversity International in 11 countries throughout Africa, the Americas and Asia Pacific. The aim is to build more resilient and adaptable farming and seed systems by exposing farmers to more crop varieties, increasing their first-hand knowledge of different traits (yield, taste, drought resistance etc.) and improving their capacity to save and access good quality seeds or planting materials. While each country operates slightly differently, a key feature is working with local partners and farmers to decrease their vulnerability to climate change and other risks by using the diversity that exists within important crops. In Papua New Guinea, Bioversity International works with the National Agricultural Research Institute (NARI) on two main crops: sweet potato and taro. NARI’s genebanks hold around 850 taro accessions (samples of plant material) and over 1,300 sweet potato accessions from around the country. Researchers from the initiative began by characterizing the traits of these accessions, while at the same time, using Geographic Information Systems (GIS) technology to predict future climate scenarios in different parts of the country. The idea was to combine the two sets of information and shortlist crop varieties that would be most useful for farmers to adapt to climate change.